1994
DOI: 10.1002/jcu.1870220408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the thyroid gland in hospitalized, chronically III geriatric patients: Thyroid volume, its relationship to age and disease, and the prevalence of diffuse and nodular goiter

Abstract: Ultrasongraphy of the thyroid gland was performed in a screening study of 177 chronically ill, hospitalized geriatric patients older than 60 years of age, from an area with only moderate iodine deficiency. The normal reference ranges of thyroid volume for males (1.7 mL to 22.2 mL) and for females 2.4 mL to 20.9 mL) were similar. The thyroid volume decreased with age in the euthyroid group and was also smaller in euthyroid females in bad health. The prevalence of goiter and thyroid nodules were 7.9% and 11.3%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…In a Hungarian geriatric population a significant decrease in ultrasonographically determined thyroid size was found that correlated with the severity of chronic disease (19). In earlier ultrasound studies Hegedu È s had already reported that thyroid size can be influenced by NTI (20).…”
Section: Discussionmentioning
confidence: 90%
“…In a Hungarian geriatric population a significant decrease in ultrasonographically determined thyroid size was found that correlated with the severity of chronic disease (19). In earlier ultrasound studies Hegedu È s had already reported that thyroid size can be influenced by NTI (20).…”
Section: Discussionmentioning
confidence: 90%
“…In a clinical context, overt hypothyroidism is preceded by a period of subclinical thyroid dysfunction, with a range of nonspecific symptoms that can be confounded with other geriatric syndromes (27) and may, as a consequence, be undertreated (28,29). According to some authors, the volume of the thyroid decreases with aging (6)(7)(8)24). Although the mean thyroid volume in the overall cohort was deemed appropriate according to the criteria adopted in our study, we observed that 20.5% of our oldest-old individuals had a reduced thyroid volume and 1.2% had goiter (> 20 mL).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates thyroid atrophy. In hospitalized euthyroid geriatric patients, the thyroid volume is also decreased, and patients in bad health display a smaller thyroid volume than those in good health 269 . However, in patients with AN there is no correlation between thyroid volume and lean body mass 267 .…”
Section: The Thyroid Axismentioning
confidence: 99%